An Experimental and Analytical study of Fatigue Crack Shape Control by Cold Working - Brennan, Feargal P.; Ngiam, S. S.; Lee, C. W. (Elsevier, 2008)
This paper presents an experimental and analytical study of crack shape evolution in steel specimens under cyclic loading. It is widely known that the introduction of compressive residual stresses by cold working the surface can be highly beneficial in improving the fatigue performance of structural components. Although it is recognised that relaxation of surface compressive residual stress can reduce the potential benefits, the effects of residual stress on crack shape evolution are often overlooked. A recently developed technique termed controlled stitch cold working, which applies differing intensities of compressive residual stress at specific regions in a structure, is shown in the paper to considerably influence fatigue crack propagation by containing crack propagation in one primary direction.
Keywords: Residual stress; Crack shape control; Fatigue; Surface crack; Cold rolling; RMS Stress intensity factors